How Work Family Conflict, Work-Life Balance, and Job Performance Connect: Evidence from Auditors in Public Accounting Firms - Rini, Rini; Yustina, Andi Ina; Santosa, Setyarini (Jurnal ASET (Akuntansi Riset), 2020)
This research examines whether work-family conflict (both work-interfering family and family interfering work) among auditors in public accounting firms affects their job performance and whether the effect is mediated by work-life balance. A web-based survey is used in deploying and delivering questionnaires to 239 auditors in public accounting firms. The result shows that work-life balance partially mediated the relationship between work-family conflict with job performance. The result also demonstrates that work interfering-family (WIF) has a negatively significant effect on work-life balance, whereas family-interfering-work (FIW) has positively related to work-life balance. This study suggests that by embrace visions that support work and personal life balance with managers and supervisors as the gatekeepers in public accounting firms to maintain subordinates' life commitments will help to minimize the occurrences of work-family conflict that will slowly reduce the possibility of poor job performance.